Grassy patch size and structure are important for northern Eastern Bristlebird persistence in a dynamic ecosystem. (3rd July 2018) - Stone, Zoë L.; Tasker, Elizabeth; Maron, Martine
ABSTRACT: Reintroductions are a critical tool for threatened species' conservation, and their success will depend on correctly identifying the key habitat requirements needed for persistence. The Critically Endangered, isolated northern population of the Eastern Bristlebird has declined to an estimated 40 individuals. A successful captive breeding programme means that future reintroductions are likely; however, knowledge of fine-scale habitat requirements associated with persistence is limited. To inform reintroduction efforts we compared habitat attributes of currently occupied and historically occupied habitat patches. Persistence was highly dependent on the extent of contiguous grassy habitat, with larger patches more likely to contain bristlebirds. This association was contingent on grass structure, with less chance of bristlebirds occurring at large sites lacking a tall, thick grassy understorey. Topographic and environmental heterogeneity within large habitat patches likely allows unburnt habitat to persist following fire, increases the temporal availability of prey and allows persistence of a population. For a largely ground-dwelling species, the presence of tall, thick grasses is expected to provide important shelter for foraging and nesting activities. Use of appropriate fire to maintain large contiguous patches with a thick, tall grassy ground layer will be critical for the continued persistence and successful reintroduction of the northern Eastern Bristlebird.